Classic Choroidal Neovascularization in Young Man: Poster Presentation - Case Report - Resident - Mawarasti, Burhana; Augiani, Amani Sakinah; Pratiwi, Rianti Wulandari; Djatikusumo, Ari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Classic choroidal neovascularization (CNV 2) represent a pathological growth of blood vessels and can result in loss of visual function. The most common cause of CNV 2 in elderly patients is age- related macular degeneration, meanwhile in young age it is frequently due to inflammation, high myopia, angioid disks and hereditary disorders. Hence, the presented case reports the characteristic findings as well the management of the disease. Case Illustration : A 37-year-old man had two weeks history of metamorphopsia on both eyes. The left eye (LE) had a worse visual acuity, macular fibrosis with pigment epithelial detachment in funduscopy and Optical Coherence Tomography (OCT). A submacular hemorrhage and exudative lesion were recognized on the right eye (RE) with type 2 choroidal neovascularization. Fundus Fluorescence Angiography (FFA) was also performed. Systemic conditions were unremarkable. Intravitreal anti-VEGF injections on RE were given for three consecutive months and showed significant improvement. Discussion : The etiology of CNV 2 includes high myopia, and inflammation. However, none was found in this patient. Nonetheless, CNV type 2 is still uncommon in young age without predisposing conditions. As most common lesions involve the macula, symptoms shown include metamorphopsia, central scotoma and floaters. FFA is still considered to be the gold standard to differentiate the types of choroidal vascularization. Neovascularization and submacular hemorrhage can be treated with intravitreal injection of anti-VEGF, as previous studies reported significant improvement. Conclusion : This was a case of bilateral CNV type 2 in a young man without any previous predisposing conditions. Three monthly injections of anti-VEGF showed significant improvement.